PENGARUH KUALITAS PRODUK, KREATIVITAS IKLAN DAN DAYA TARIK TERHADAP KEPUTUSAN PEMBELIAN WARDAH DI SHOPEE - Hermalina Boru Hasibuan; Mauli Siagian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Due to the fierce rivalry brought about by Indonesia's beauty industry's explosive growth, customer choices play a crucial role in a brand's success. A number of elements, such as the attractiveness of the goods, the inventiveness of the advertising, and the quality of the product itself, impact these purchase decisions. The purpose of this study is to examine how consumers' decisions to buy Wardah products—one of the top halal cosmetic brands available on the Shopee e-commerce platform—are influenced by factors such as product quality, creative advertising, and attractiveness. Regression analysis techniques are used in this study's quantitative approach to examine the hypotheses. Information was gathered from customers who bought Wardah goods on Shopee. The results of the study show that attraction, advertising originality, and product quality all significantly and favorably affect consumers' decisions to buy. Additionally, concurrent research demonstrates that attraction, advertising originality, and product quality all significantly impact consumers' decisions to buy Wardah items on Shopee.